2022
DOI: 10.1182/blood.2021014966
|View full text |Cite
|
Sign up to set email alerts
|

S100A8/A9 drives the formation of procoagulant platelets through GPIbα

Abstract: S100A8/A9, also known as calprotectin or MRP8/14, is an alarmin primarily secreted by activated myeloid cells and platelets with anti-microbial, pro-inflammatory and pro-thrombotic properties. Increased plasma levels of S100A8/A9 in thrombo-inflammatory diseases are associated with thrombotic complications. We assessed the presence of S100A8/A9 in the plasma and lung autopsies from patients with COVID-19 and investigated the molecular mechanism by which S100A8/A9 affects platelet function and thrombosis. S100A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 79 publications
4
21
0
Order By: Relevance
“…Here, we found that S100A8/A9 protein levels were enhanced by more than 4-fold (log2 fold change of 2.25) in platelets in COVID-19 patients. As platelet transcript levels in COVID-19 patients were unchanged [21], this is likely to be the result of enhanced platelet binding and uptake of plasma S100A8/A9, potentially through GPIb/CD36 receptor interaction [66]. The enhanced basal platelet PS exposure in COVID-19 patients detected in our study would be consistent with this.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Here, we found that S100A8/A9 protein levels were enhanced by more than 4-fold (log2 fold change of 2.25) in platelets in COVID-19 patients. As platelet transcript levels in COVID-19 patients were unchanged [21], this is likely to be the result of enhanced platelet binding and uptake of plasma S100A8/A9, potentially through GPIb/CD36 receptor interaction [66]. The enhanced basal platelet PS exposure in COVID-19 patients detected in our study would be consistent with this.…”
Section: Discussionsupporting
confidence: 83%
“…However, we cannot rule out that COVID-19 conditions may induce platelet P-selectin expression in the absence of integrin α IIb β 3 activation, such as has recently observed in a small fraction of CRP/PAR-1 activated platelets [70]. The recent study by Colicchia et al [66] is also of interest as they demonstrated that S100A8/A9 can induce P-selectin expression whilst inducing an integrin α IIb β 3 activatory state that lacked aggregatory ability and had low-fibrinogen binding capacity.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, we confirm the expression of the TLR4/MD2 receptor on the surface of platelets ( Supplementary Figure S2B ), as has been described previously [ 32 ]. Recent studies have shown that high concentrations of S100A8/A9 are able to induce direct platelet activation via TLR4 and GPIbα [ 28 , 33 ]. Since TLR4 is known as the counterreceptor to S100A8/A9 heterodimers, we stimulated platelets with mutated S100A8/S100A9N70AE79A heterodimers unable to form tetramers, and could confirm GPIIbIIIa—but not CD62P—upregulation ( Supplementary Figure S2C ).…”
Section: Resultsmentioning
confidence: 99%
“…Expression levels were investigated in a FACSCantoII flow cytometer (BD Bioscience). Stimulation of isolated WT platelets with S100A8/A9 tetramers was performed according to Colicchia et al with minor modifications [ 28 ]. Murine platelets were isolated via repetitive slow-speed centrifugation and resuspended in Tyrode’s buffer (20 mM HEPES, 136 mM NaCl, 2.6 mM KCl, 12 mM NaHCO 3 , 5.5 mM D-glucose, 2 mM CaCl 2 , 1 mM MgCl 2 ).…”
Section: Methodsmentioning
confidence: 99%